Environmental distribution of polyhydroxyalkanoate (PHA) production in the domain Archaea (Acta Scientiarum. Biological Sciences, 2025)
Polyhydroxyalkanoates (PHAs) are polyesters synthesised by prokaryotes as a carbon and energy storage strategy. Due to their properties and versatility, these biopolymers are a potential alternative to conventional low-caliber plastics. However, the cost of the process, particularly the carbon sources used as raw materials, limits their large-scale production. The study of new production strains isolated from underexplored sites may be a viable option to improve production capacity. The genes encoding PHA production are organized in the phaCAB operon, with phaC being the key enzyme for polymerization. In this study, we analyzed the environmental distribution of the phaC gene in Archaea using bioinformatic tools to demonstrate the relevance of searching for archaeal strains for PHA production. We searched NCBI for PhaC synthase protein sequences in cultured Archaea and metagenomes. We found 176 sequences of PhaC synthases in cultured Archaea and 66 in metagenomic proteins. Twenty environmental categories were defined based on the associated environmental information. No changes were necessary to ensure grammatical correctness.  PhaC genes were found in 41 archaeal genera and 7 possible genus candidates, with Nitrosopumilus sp. being the most abundant genus. The distribution of phaC genes was mainly associated with sediments and marine environments, with less presence in soil niches. These results contribute to the knowledge of the taxonomic diversity and habitats where the phaC gene is present in Archaea with potential for polyhydroxyalkanoate production.